The development of craft beer produced from de-fatted yellow nutsedges and the impact of various packaging materials on its preservation quality throughout its shelf life - Xiao-Kun Jiang; Lei Zhang (CyTA - Journal of Food)
In this study, we utilized defatted yellow nutsedges meals as raw material to develop a craft beer and subsequently analyzed preservation quality throughout its shelf life. Our study determined that the optimal fermentation conditions for the craft beer included the use of Saaz hops, US-04 yeast, and the addition of 15% de-fatted yellow nutsedges. Under these conditions, the resulting beer exhibited an alcohol content of 4.50%, a foam retention time of 224.00 seconds, a color measurement of 10.00 EBC, a total acid content of 1.70 mL/100 mL, and a bitterness level of 22.15. Compared to glass bottles (GB) and aluminum cans (AC), the aroma content of craft beer packaged in polyethylene terephthalate (PET) bottle was lower, while the diacetyl levels were higher on shelf life. Meanwhile, the activity of protease A exhibited a notable increase in PET bottle packaging, in comparison to GB and AC packaging.